The longest duration of retention of a video capsule. (8th July 2014) - Harrington, Chris; Rodgers, Colin
Abstract : An underweight 15-year-old boy had a video capsule endoscopy (VCE) to investigate iron deficient anaemia associated with elevated platelet and white cell counts. The suspicion was of subclinical small bowel Crohn's disease after the findings of a radiolabelled white cell scan. The VCE in May 2007 found patchy inflammation and superficial ulcers in the terminal ileum consistent with Crohn's disease. By March 2008, the patient remained asymptomatic but the capsule had not passed. He was treated with steroids to improve the inflammation and allow the capsule to pass. This was unsuccessful. Abdominal X-rays appeared to show that it was in the rectum. CT of the abdomen and pelvis in July 2012 showed that it was actually in the mid-distal ileum within a mass of inflamed and matted small bowel loops. He was last reviewed in March 2014. He has now retained the capsule asymptomatically for 6 years and 10 months.